2020
DOI: 10.5688/ajpe7890
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Student Failure or Poor Performance on Advanced Pharmacy Practice Experiences

Abstract: Objective. To determine factors predictive of student failure or poor performance on advanced pharmacy practice experiences (APPEs) at a single pharmacy program. Methods. This retrospective cohort evaluated students entering the Doctor of Pharmacy (PharmD) program from 2012-2014 at St. Louis College of Pharmacy. Students who received a grade of F for one or more APPEs (failure group) were compared to all other students (non-failure group). A secondary evaluation compared students with a C or F on one or more A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Beyond course failures, this tutoring program could be used as an intervention to provide academic support and minimize the need for course remediation which may have an impact in the experiential curriculum as poor academic performance, including failures and lower grade point averages, is a risk factor associated with failure or poor performance on advanced pharmacy practice experiences. 26 Currently, existing studies on PAL in the pharmacy literature evaluated students' perceptions, skills gained, and attitudes. 7,[10][11][12][13]18,19,21,22 Rodis and colleagues conducted a survey and reported that a majority of students agreed that the student-peer mentoring o n a drug information question improved the likelihood of tutees receiving a higher grade.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond course failures, this tutoring program could be used as an intervention to provide academic support and minimize the need for course remediation which may have an impact in the experiential curriculum as poor academic performance, including failures and lower grade point averages, is a risk factor associated with failure or poor performance on advanced pharmacy practice experiences. 26 Currently, existing studies on PAL in the pharmacy literature evaluated students' perceptions, skills gained, and attitudes. 7,[10][11][12][13]18,19,21,22 Rodis and colleagues conducted a survey and reported that a majority of students agreed that the student-peer mentoring o n a drug information question improved the likelihood of tutees receiving a higher grade.…”
Section: Discussionmentioning
confidence: 99%
“…First, investigators have raised the issue of whether performance within the didactic curriculum (as measured by grades) correlates to performance in clinical settings. [14][15][16] Second, some have questioned whether in clinical settings if Pass/Fail grading systems might be more logical as compared to traditional A-F grading scales. [17][18][19][20] Call and colleagues aimed to determine factors predictive of student failure or poor performance on APPEs by conducting a retrospective cohort study comparing students who failed any APPE to students who did not between 2012-2014.…”
Section: Do Classroom Grades Align With Clinical Performance?mentioning
confidence: 99%
“…[17][18][19][20] Call and colleagues aimed to determine factors predictive of student failure or poor performance on APPEs by conducting a retrospective cohort study comparing students who failed any APPE to students who did not between 2012-2014. 14 A total of 669 students at a single pharmacy school were included in the analysis with 28 students (4.2%) failing…”
Section: Do Classroom Grades Align With Clinical Performance?mentioning
confidence: 99%
“…Call et al examined a range of factors, including GPA; course grades; performance-based assessment and exam scores; professionalism issues on IPPEs; and academic honor code violations. 4 Nyman et al analyzed the predictive value of student demographics, along with admission and didactic performance measures. 5 Both of these studies found that two factors correlate to APPE readiness more than others: aggregate pharmacy education knowledge-based variables and entering age of students (more than skills-based variables, admission measures, or other student demographics).…”
Section: Introductionmentioning
confidence: 99%
“…5 Both of these studies found that two factors correlate to APPE readiness more than others: aggregate pharmacy education knowledge-based variables and entering age of students (more than skills-based variables, admission measures, or other student demographics). 4,5 Medical educators have also examined indicators that are predictive of medical student performance. Efforts have focused on 4 general categories, including demographics (e.g., gender), other background factors (e.g., college major), performance/aptitude (e.g., medical college admission test scores), and noncognitive factors (e.g.…”
Section: Introductionmentioning
confidence: 99%